TRADISI BARU: KAJIAN SEMIOTIKA LOTMAN DAN DEKONSTRUKSI ATAS NOVEL PUTRI KARYA PUTU WIJAYA - , Muh. Khairussibyan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Putri as a novel that addressing locality of Bali was less widely discussed than others experimental works of Putu Wijaya. Several researches that studied on Putri were dominated by the perspective of feminism without reviewing the structure of the novel as a whole worldview and without any attempt to criticize the idea of the novel. Lotmanâs semiotic theory and deconstruction approach are the right theoritical perspectives to expose and criticize the structure of the novel and to enhances the previous studies. Lotman states that secondary modeling system is a reflection of two-way reflection, that is reflection of reality at once a reflection of the author's consciousness. Both of these reflection implies the existence of a relationship between the extra text structure and intra text structure. While the deconstruction approach used to assess the non sistemic world view of the novel. Semantic fields that make up the structure of Putri were equivalence to each other. All of the semantic fields were variants of rational vs. irrational invariant which is arciseme in semiosphere of modernism. The worldview of modernism opposed to the worldview of traditionalism of Bali. Modernism and traditionalism of Bali in Putri connected to modernism and traditionalism of Bali beyond the text based on the principle of the aesthetic of identity and the aesthetic of contrast. Traditionalism of Bali in the text was repositioned by the view point of modernism. It makes this novel as a pheripheric text that was dominated by the aesthetic of contrast. The worldview of Putri also reflects the social structure and history of modern Balinese that was struggle for decades between modernism and traditionalism of Bali which gave birth to new middle class in Bali. The idea of New Tradition in Putri provides the ideas for the middle class to achieve progress and also avoids feeling cut off from the roots of Balinese culture. Deconstruction study show that this novel denies the basic structure of itself that were rationality and tradition without any personal interest.